Non-Polynomial Spline Solution For Bratu's Problem - Özer, Mehmet; Çağlar, Hikmet; Hacıbekiroğlu, Gürsel (Int Scientific Conference Sgem, 14, Kilment Ohridsky Blvd, Sofia, 1797, Bulgaria, 2010)
In this paper, we have discussed a third-degree non-polynomial spline solution for the numerical solution to nonlinear boundary value problems (BVPs) and compare other metods. Two numerical examples are given to illustrate the efficiency and performance of the method. The method gives accurate results in both the linear and nonlinear cases.
Keywords: Bratu's problem; Non-Polynomial Spline; Boundary-Value-Problems; Numerical-Solution; Gelfand Problem; Equations; Bratu sorunu; sınır değer problemleri; Sayısal-Çözüm; Gelfand Sorunu; denklemler